Antioxidant Activity and Phenolic Content of Streblus asper Leaves from Various Drying Methods - Nor Mawarti Ibrahim; Ishak Mat; Vuanghao Lim; Ruzita Ahmad (MDPI AG, 2013)
Aqueous and ethanol extracts of oven and freeze-dried Streblus asper leaves were investigated using DPPH assay. The presence of phenolic compounds and flavonoids in the extracts, which were detected by Folin and colorimetric assays, respectively, may be responsible for the antioxidant activities of S. asper. The different drying treatments resulted in significant differences (p < 0.05) in the antioxidant properties as well as the phenolic and flavonoid contents of the S. asper extracts. Freeze-dried S. asper leaf extracts exhibited high DPPH radical scavenging activity ranging from 69.48% ± 0.03% to 89.25% ± 0.01% at concentrations ranging from 0 to 1 mg/mL, significantly higher compared with the oven-dried extracts which were in the range of 68.56% ± 0.01% to 86.68% ± 0.01%. Generally, the 70% ethanol extract of the freeze-dried samples exhibited higher phenolic and flavonoid content than the aqueous extract, with values of 302.85 ± 0.03 mg GAE/g and 22.70 ± 0.02 mg QE/g compared with 226.8 ± 0.03 mg GAE/g and 15.38 ± 0.05 mg QE/g, respectively. This study showed that S. asper leaf extracts contain a number of health promoting bioactive compounds, such as phenolic compounds, and are potential sources of natural antioxidants.